BIOAVAILABILITAS DAN SPESIASI LOGAM BERAT Pb DAN Cd PADA TANAH PERTANIAN BASAH DAN KERING DI DAERAH DENPASAR - I Made Siaka; Emmy Sahara; Gusti Agung Putu Merta Dharmayoga (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
A research on the bioavailability and speciation of Pb and Cd in wet and dry soils in some agricultural areas in Denpasar has been carried out. Samples were taken from agricultural land in Peguyangan and Kesiman areas. This study was aimed to determine the total metal concentrations and the fractions of the species of Pb and Cd, as well as the level of the metal bioavailabilities. The study included the determination of the total Pb and Cd concentrations in the samples and extraction of the metal through the application of the sequential extraction technique followed by measurement of the metal with the Atomic Absorption Spectrophotometer. The result showed that generally the concentrations of Pb and Cd total in the wet soil from the two sampling areas were higer than those of the dry soil which were varied between 14,0484-16,1072 mg/kg and 1,5983-1,9885 mg/kg respectily.the results for Pb speciation in wet and dry soils from both locations as follows : the bioavailable fraction (EFLE fraction) and potentially bioavailable (consisting of Fe/Mn oxides and organic-sulfide fractions) were of 29,81%-83,66% and 2,44%-13,96 %, respectily, while the resistant (non-bioavailable) fraction were of 28,55%-55,11%. The results for Cd speciation in wet and dry soils from both locations were as follows : the bioavailable an potentially bioavailable fractions were of 28,62%-67,87% and 7,63%-48,39%, repectily, while the resistant (non-bioavailable) fractions were of 10,68%-30,92%.